Abandoned child's right to identity protection in Malaysia - Mohd, Azizah (David Publishing, 2011)
The law on protection of the rights of a child including the abandoned child (foundling) in Malaysia was reformed by virtue of the Child Act 2001 quite immediately after ratification of the United Nations Convention on the Rights of the Child (UNCRC) by the Malaysian government in 1995. Besides the fact that the Child Act 2001 is enshrined with the spirit of the UNCRC, provisions on protection of the rights of the abandoned child to identity are missing and scattered in other statutory provisions. This paper seeks to discuss the law relating to the protection of the rights of the abandoned child to identity especially to name, registration of birth and citizenship under the civil and Islamic law in Malaysia and under the Shari’ah. The paper will examine the extent to which the law can provide just and equitable rules in protecting the rights of the abandoned child in those matters. The discussion will also highlight the provisions under the UNCRC which emphasizes on the obligation of the State Party to protect a child’s identity which includes his name, nationality and family ties. Finally, the paper will provide comments and suggestions to improve the current law in Malaysia, if any.